(untitled) (The Pretoria Student Law Review, 2021)
The main research problem that will be addressed is the reasons why a patriarchal system of law developed. This will be addressed by looking at the shifts in natural law, the rise of positivism and modernity and thus a restricted jurisprudence all of which contributed to a male dominated system to the exclusion of females.